The “Automobile Religiosity” in Iran: A Study on Religious Meanings and Functions of Automobile in Contemporary Tehranian Culture - Asadi, Siavash; Hooshangi, Tahereh (Society & Sustainability, 2019)
Although the automobile has had common functions among various cultures, some unique patterns of car consumption, as secondary functions, appear in each society proportional to cultural and social backgrounds. What makes "the automobile in Iran" different is that it has been transformed into a religious object affected by society's religious structure. The present paper endeavors to find motivations and manners of this transformation to decoding religious semiology and categorize religious functions of the automobile. To achieve the deepest layer of consumers' motivations, a qualitative method in the framework of grounded theory was chosen. We collected our data by deep semi-structured interviews with car consumers in Tehran, in addition to field observations, pictures and films. These data were analyzed in an analytical-descriptive method. The study led us to the main category saying that the automobile represents religious identity. This is usually exposed by two main strategies, the inside automobile activities and manipulating of the automobile's appearance, and is revealed in three models of secondary function: resistive, confirmative, and privacy function. These functions represent a new religiosity in Iran that can be called the “automobile religiosity.”